2019
DOI: 10.1111/edt.12468
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the mandibular gonial angle on the occurrence of mandibular angle fracture

Abstract: Background/Aims Angle fractures represent the largest percentage of mandibular fractures. They pose as a unique entity because of their codependent morphological dynamic factors, rendering the understanding of the mechanism, and treatment challenging. The aim of this study was to analyze the association between the mandibular gonial angle and the risk of mandibular angle fracture while highlighting its clinical relevance. Materials and Methods A retrospective analysis of radiographs of patients treated for man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 19 publications
5
18
0
3
Order By: Relevance
“…The mandibular gonial angle has a significant implication to other anthroporadiometric values of the mandible, which include mean cortical thickness, panoramic mandibular index, mandibular height, and intensity of muscle pull. [ 4 9 10 ] It is an important anthropometric feature which contributes to facial esthetics and biodynamics of masticatory musculature. In practice, gonial angle is assessed by radiographic analysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The mandibular gonial angle has a significant implication to other anthroporadiometric values of the mandible, which include mean cortical thickness, panoramic mandibular index, mandibular height, and intensity of muscle pull. [ 4 9 10 ] It is an important anthropometric feature which contributes to facial esthetics and biodynamics of masticatory musculature. In practice, gonial angle is assessed by radiographic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Although lateral cephalogram is the preferred radiograph used to determine the gonial angle, OPGs were used in both the studies, as they are the established norm of assessing angle fractures and were the only available data. [ 1 4 ] The accuracy of OPG in assessing the gonial angle has been established by a study conducted by Bhullar et al . [ 11 ] Studies indicated that OPGs provide more precise measurement of the gonial region, as they do not demonstrate overlap of right and left angles, as observed in lateral cephalograms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kondisi ini terjaya sejakan dengan nilia MCW yang diperoleh. Hal ini sesuai dengan penelitian yang dilakukan oleh Vasantha Dhara.et al, 18 yang menyatakan bahwa individu dengan sudut gonial besar memiliki nilai MCW lebih rendah, hal ini menunjukkan kurangnya kualitas tulang rahang di daerah sudut mandibula sehingga meningkatkan potensi terjadinya fraktur. 18 Sebaliknya, hasil pengukuran nilai GA pada prajurit berusia 40-58 tahun ternyata lebih tinggi dibanding non prajurit, hal ini kemungkinan faktor psikologis dari prajurit ternyata juga mampu mempengaruhi pertmbuhan dan perkembangan dari tulang.…”
Section: Laporan Penelitianunclassified